2007
DOI: 10.1080/10739680701410389
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Inhibits Reduced Arteriolar Conducted Vasoconstriction in Septic Mouse Cremaster Muscle

Abstract: These data indicate that early and delayed intravenous boluses of ascorbate prevent/reverse sepsis-induced deficit in arteriolar conducted vasoconstriction in the cremaster muscle by inhibiting nNOS-derived NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Indeed, in iNOS knockout and NADPH oxidase-deficient mice, LPS induced much less production of NO and superoxide, respectively (7,26). Moreover, CLP remarkably increases nNOS activity without affecting nNOS protein expression in mouse skeletal muscle (34). The results from the present study indicate that both NADPH oxidase and eNOS uncoupling are responsible for stimulation by CLP of superoxide production and that both iNOS and nNOS activity generate the excessive NO in septic skeletal muscles.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, in iNOS knockout and NADPH oxidase-deficient mice, LPS induced much less production of NO and superoxide, respectively (7,26). Moreover, CLP remarkably increases nNOS activity without affecting nNOS protein expression in mouse skeletal muscle (34). The results from the present study indicate that both NADPH oxidase and eNOS uncoupling are responsible for stimulation by CLP of superoxide production and that both iNOS and nNOS activity generate the excessive NO in septic skeletal muscles.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, this is a dynamic process, as capillaries in which there is no flow at a given time may be perfused a few minutes later. These alterations have been reported after administration of endotoxin or live bacteria and during bacterial peritonitis, 8 , 9 , 11 and have been observed in rodents 12 , 13 as well as in large animals 9 , 11 . In addition, all studied organs have been affected, including the skin, 14 muscle, 12 , 13 eye, 15 tongue, 9 gut, 9 , 10 liver, 7 heart, 16 and even the brain 11 .…”
Section: Microcirculatory Alterations In Sepsis: Where Is the Evidence?mentioning
confidence: 77%
“…Most of the reports assigned the effects observed in vivo to MnTBAP 3À SOD-like activity. Only two ''shy'' reports claimed no effects with MnTBAP 3À (172,214). We have clearly shown that MnTBAP 3À is not an SOD mimic, as it has negligible SODlike activity (log k cat ¼ 3.16) (31,264).…”
Section: Electrostaticsmentioning
confidence: 80%